utilization of Lead citrate on the peripheral Nervous Systemin Rat (An Experimental and Histological Study) (Tikrit Journal of Pharmaceutical Sciences, 2023)
administrated of lead citrate solution with phosphate buffer saline orally in a dose of 250 mg/kg for thirty days. Animais were divided into four groups. Group A survived for 30 days. Group B for 60 days. Group C fbr 90 days and Groupb tzO days. Twenty animals were administrated phosphate buffer saline for 30 clays and classified into four 4 groups and survived for 30,60,90 and 120 days afterthe last dose. Atthe end of eachperiod the animals were scarified and segments of the peripheral nerve (Sciatic nerve) were removed and fixed in osmic acid 1o/o , then processed in graded glycerin 500/o , pure glycerin for obtaining teased nerve fibers . Specimens tbr miiror"opi" examination were done by application of the histological technique for obtaining transverse and longitudinal sections of the 6um thickness. The results of the present itr,iy d"*onstrated that the peripheral nerve fibers were affected after the 30,and 60 days mostly reflected by the presence of the wallerian degeneration ( destrr-rction of the myelin sheath ancl axon) of the most nerve fibers and at the period of 90 days after the last dose was indicated a regeneration of the most nerve fibers , but still there cerlain percentage of the degeneratecl nerve f-rbers and irregular outlines of its myelin sheath. After 120 days, Remyelination of most nerve fibers were detected associated with short internodes in between other intact nodes of Ranvier .